1999
DOI: 10.1111/j.1651-2227.1999.tb01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to methylphenidate in boys with attention‐deficit hyperactivity disorder

Abstract: The response to methylphenidate was examined in 36 boys, aged 7–11 y, with attention‐deficit hyperactivity disorder (ADHD) in a double‐blind, placebo‐controlled, crossover design. Hyperactivity and conduct problems were significantly reduced during methylphenidate treatment. Stimulant medication was associated with improvements on tests of sustained attention, working memory and motor steadiness. When individual changes were studied, it was found that 83% showed a significant improvement in their hyperactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 18 publications
0
18
0
1
Order By: Relevance
“…42,91 In addition to these studies, two reported measuring hyperactivity for parents and teachers using a Conners' questionnaire, 46,68 and one measured hyperactivity only using the CTRS. 98 Five of the studies also measured hyperactivity using additional scales. 42,43,68,91,98 Table 6 presents the means and SD for the results of these studies (where reported).…”
Section: Tervo and Colleagues 2002mentioning
confidence: 99%
See 1 more Smart Citation
“…42,91 In addition to these studies, two reported measuring hyperactivity for parents and teachers using a Conners' questionnaire, 46,68 and one measured hyperactivity only using the CTRS. 98 Five of the studies also measured hyperactivity using additional scales. 42,43,68,91,98 Table 6 presents the means and SD for the results of these studies (where reported).…”
Section: Tervo and Colleagues 2002mentioning
confidence: 99%
“…98 Five of the studies also measured hyperactivity using additional scales. 42,43,68,91,98 Table 6 presents the means and SD for the results of these studies (where reported). Two of the studies used a parallel design.…”
Section: Tervo and Colleagues 2002mentioning
confidence: 99%
“…Several studies have attempted to predict MPH efficacy using clinical characteristics including age (Buitelaar et al, 1995;Zeiner et al, 1999), IQ (Buitelaar et al, 1995), symptoms, disorder severity (Buitelaar et al, 1995;Zeiner et al, 1999), and neuropsychological test scores (Lee et al, 2009). Recently, more objective biomedical predictors (Hermens et al, 2006) of brain function Cho et al, 2007;Ilgin et al, 2001;la Fougere et al, 2006;Sangal and Sangal, 2004;Schweitzer et al, 2003) have been used (see also Supplementary Materials).…”
Section: Introductionmentioning
confidence: 99%
“…The ADHD literature has revealed that the most consistent predictors of a positive response to stimulants include higher levels of attention deficiency (8)(9)(10)(11), higher levels of hyperactivity (10,12,13), younger age (8,11), and higher intellectual functioning (8,14,15). The most consistent predictor of a negative stimulant medication response is comorbidity of internalizing psychopathology (8,13,16,17).…”
Section: Introductionmentioning
confidence: 99%